Cotidiano, ética e saúde: o serviço social frente à contra-reforma do Estado e à criminalização do aborto - Matos, Maurílio Castro de (2009)
This thesis has as an objective to reflect about the everyday life of the work of social workers in health politics. For this, it elects two axles of analysis: the counter-reform of State in health politics and the criminalization of the abortion in Brazil. It is structured in three parts, besides an introduction and the final consideration. In the first part it s showed a historical view and is presented contemporary questions that made their marks in the health politics and the issue of the abortion in Brazil. In the second part, are being developed reflections about the Social Work, first in the perspective of collective labor in health area and the challenges that are in this. After are undertaken reflections about the everyday life and ethics and the rebeats in the profession of social worker. In the third part are presented the results of our research, realized inside a large hospital of SUS in Rio de Janeiro State. First, it has been realized a characterization of the Social Work sector as a whole and after has been analyzed interviews realized with social workers that directly deal with women, in their health issues, in this hospital. This thesis intend to contribute for the critical reflection about the everyday of the work of social workers in the health politics, as well as put forward questions about the importance of SUS, in the original perspective of the social movement of the Sanitary Reform, and of the decriminalization of the abortion in Brazil